Airborne Piezoelectric Micromachined Ultrasonic Transducers for Long-Range Detection - Luo, Guo-Lun; Kusano, Yuri; Horsley, David A. (Journal of microelectromechanical systems, 2021)
This paper presents an airborne piezoelectric micromachined ultrasonic transducers (PMUTs) operated at low frequency (40-50 kHz) for long-range detection, where the acoustic absorption loss in air is relatively low (0.8-1 dB/m). The PMUTs made with single-crystal Lead Zirconate Titanate (PZT) enables a high piezoelectric coefficient ( {e} _{31, f} ≈ ~16 - 24 C/ \text{m}^{{2}} ), and a low dielectric constant ( ε _{r}~≈ ~308 ), achieving high PMUT transceiver efficiency. The 2× 2 PMUT array achieves a very high sound pressure level (SPL) output of 109.4 dB at 26 cm distance. Different from conventional PZT PMUTs, this study utilized single-crystal PZT with a low permittivity to achieve a good acoustic reception, demonstrating the sensitivity of 2 mV/Pa. This work reports the PMUT design, modeling, fabrication, characterization, enabling a long-range detection of 4.8 meters in a pulse-echo experiment, which was conducted by a pair of 2× 2 PMUT arrays with the matched resonances. [2020-0270]